Determinan status partisipasi pendidikan anak usia dini di Pulau Jawa tahun 2019 - Aisyah Salsabila; Budyanra Budyanra (Research Centre for Population, National Research and Innovation Agency (BRIN), 2022)
Early childhood education is essential in the initial education process and in forming self-foundation. Java Island was the island with the highest average early childhood education gross enrollment rate in Indonesia in 2019. However, the difference in early childhood education gross enrollment rate between regions in Java is also the largest. The economic and socio-demographic conditions that support successful participation at the regional and household levels are not much different. This study aims to determine the general description of early childhood education participation status in Java in 2019, along with the determinants and trends of the variables that influence it. The analytical method used is multilevel binary logistic regression analysis using data from Susenas Kor March 2019 and Dapodik PAUD Kemendikbud. The results show that the participation in early childhood education in Java is 47.47%. All variables except the status of the area of residence had a significant effect, and the tendency to participate in early childhood education was more remarkable for girls. Participation in early childhood education also tends to be greater for children living in districts/cities with a high percentage of villages with a high PAUD unit and a high ratio of educators to children aged 3-6 years.